PENGARUH PERSEPSI KEMUDAHAN DAN PERSEPSI MANFAAT TERHADAP SIKAP PENGUNAAN E-WALLET DI KOTA BANDUNG 2020 - Aldo Putra Kusuma; Syahputra Syahputra (Politeknik Negeri Batam, 2020)
Abstract This research is based on the background of related problems. With E-Wallet consumers can transfer money to the desired bank account or to fellow E-wallets. Consumers are also free to make payments for purchases made anytime and anywhere. This research aims to determine the effect of ease and benefit of using E-Wallet with TAM (Technology Acceptance Model) model to discuss a system or technology with an E-Wallet object. This research uses quantitative descriptive method with type of research is multiple regression. Sampling is carried out by non-probability sampling with type purposive sampling. Based on the results of descriptive analysis, the entire variable occupies a very good category which means that all statements are very understandable by respondents. In the results of the T test and the F test variable perceived ease of use (X1) and the perceived usefulness (X2) on attitude toward using (Y) came to the conclusion that a variable X1 and X2 have positive and significant effect on both the partial and simultaneous against Y variables. And 45.2% of attitude toward using are affected by the perceived ease of use and perceived usefulness, 54.8% are influenced by other factors. Keyword: Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, TAM (Technology Acceptance Model), E-Wallet.